Concept Map in Medical Education - Kainat Javed; Kinza Aslam; Imran Jawaad; Sadia Irshad Leghari; Qurat-Ain Leghari (Journal of Rawalpindi Medical College)
Objective: To assess and compare the proficiency of concept mapping skills among resident doctors of varying experience levels (1st, 2nd, 3rd, and 4th-year residents) before any instruction. This shift aims to produce more effective doctors who can comprehensively grasp diseases. Pakistani medical colleges have adopted these teaching reforms to enhance students' cognitive skills, encouraging them to apply knowledge to clinical scenarios for better decision-making.